(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Micronutrient deficiency is a major problem in many developing countries. Micronutrient especially Zn deficiency may affect pregnancies, delivery, and outcome of pregnancy. Objectives: To study serum Zn level in full term mother and non pregnant women in order to compare with those of non pregnant women as reference value. Method: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College Mitford Hospital, Dhaka, during the period of 1st January 2009 to 31st December 2009. A total number of 55 subjects were included in this study, among them 27 were full term delivery mothers (group B), treated as study group. Age range of full term mother was from 20-40 years. Again, 28 non pregnant women with age range from 20-30 years were taken as a control group. Statistical analysis was done by using appropriate method as applicable. Results: Mean serum Zn level were significantly lower (p<0.001) in full term pregnant mother in comparison to those of non pregnant women. Conclusions: The present study revealed a lower level of zinc in full term mother than non pregnant women. The decreased serum Zn level may be due to poor nutritional status during pregnancy as serum total protein and albumin levels were also lower in this group of subjects. http://dx.doi.org/10.3329/bjpp.v26i1-2.19960 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 17-20